Cícero: Obra e Recepção - Marcos Martinho (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2018)
The book brings together seven essays on Cicero written by specialists in the Author. The essays are grouped into two sections: the first one presents papers on Cicero's works (the dialogues: Lucullus, De finibus, De oratore, De officiis); the papers in the second one discuss on both the early and late reception of Cicero (in Seneca, Petrarch and Erasmus). The authors are professors from Brazilian (Adriano Scatolin, Bianca Fanelli Morganti, Elaine Cristine Sartorelli, Sidney Calheiros de Lima), French (Carlos Lévy) and Italian universities (Aldo Setaioli, Ermanno Malaspina). The book avoids traditional biographical approach, which tends to take the works of Cicero as a reliable witness of political and family events, sometimes distrusts them as a distorted picture of public and private actors. The essays here assembled also avoid conceiving Cicero's works as either the Author's profession of faith in a philosophical doctrine, or a tendentious presentation of the theses of philosophical schools. Instead, the contributors adopt another interpretative key, so that, when analyzing a philosophical dialogue of Cicero, instead of seeking references to its historical moment, focus on its controversial aspects (due to the dispute between the schools of philosophy), rhetorical aspects (the amplifying devices through which the Author compares the strength of one thesis with the weakness of another), fictional aspects (including the description of the scene and the picture of the characters). Thus, it can be said that the book seeks a more appropriate approach to Cicero's works, not taking them as mere source of historical knowledge, but considering their historicity, that is, the devices for discursive production of their own time.